Difference analysis of multidimensional electroencephalogram characteristics between young and old patients with generalized anxiety disorder - Wang, Jie; Fang, Jiaqi; Xu, Yanting; Zhong, Hongyang; Li, Jing; Li, Huayun; Li, Gang (Frontiers in Human Neuroscience, 2022)
Growing evidence indicates that age plays an important role in the development of mental disorders, but few studies focus on the neuro mechanisms of generalized anxiety disorder (GAD) in different age groups. Therefore, this study attempts to reveal the neurodynamics of Young_GAD (patients with GAD under the age of 50) and Old_GAD (patients with GAD over 50 years old) through statistical analysis of multidimensional EEG features and machine learning models. In this study, 10-minute resting-state electroencephalogram (EEG) data were collected from 45 Old_GAD and 33 Young_GAD. And multidimensional EEG features were extracted, including power spectral density (PSD), fuzzy entropy (FE), and phase-lag-index (PLI), on which comparison and analyses were performed later. The results showed that Old_GAD exhibited higher PSD value and FE value in beta rhythm compared to theta, alpha1, and alpha2 rhythms, and functional connectivity (FC) also demonstrated significant reorganization of brain function in beta rhythm. In addition, the accuracy of machine learning classification between Old_GAD and Young_GAD was 99.67%, further proving the feasibility of classifying GAD patients by age. The above findings provide an objective basis in the field of EEG for the age-specific diagnosis and treatment of GAD.